علم أسباب ورود الحديث: دراسة وصفية = Reasons and socio-historical background of Hadith: a descriptive study - Abdul Manas, Shayuthy; Muhammad Ibrahim, Muhammad Sadiq (Faculty of Quranic and Sunnah Studies, Universiti Sains Islam Malaysia, 2016)
The study focuses on clarifying some important aspect of “Ilm Asbab Wurud al-Hadith” which mean “Adverting of Prophetic Tradition”, by analyzing the three compound words, which are asbab, wurud and al-hadith-, beside its major three divisions which are; the apparent reason, (al-Sabab al-Zahir) the hidden reason, (al-Sabab al-Khafi) and the reason outlined (al-Sabab al-Mubayyan) by giving appropriate examples. As well as discusses the ways to understand the asbab wurud al-hadith according to the different considerations, such as the understanding by the prophet’s text, by the words of the companions, and by the personal reasoning, Futhermore the all branches which ramify from the major three ways mentioned by giving obvious examples. Moreover, it present some important benefits of “asbab wurud al-hadith”. The study is concluded by submitting fundamentals and restrictions to deal with asbab wurud al-hadith” according to the views of the scholars in the field of hadith.